2018
DOI: 10.1002/jcph.1082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flexible Tacrolimus Drug Concentration Monitoring Approach in Patients Receiving Extended‐Release Once‐Daily Tacrolimus Tablets

Abstract: The majority of United States kidney transplant patients are treated with tacrolimus, a drug effective in preventing graft rejection, but with a narrow therapeutic range, necessitating close monitoring to avoid increased risks of transplant rejection or toxicity if the tacrolimus concentration is too low or too high, respectively. The trough drug concentration tests are time sensitive; patients treated on a twice‐daily basis have blood draws exactly 12 hours after their previous dose. The schedule's rigidity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Recommendations for all CYP3A5 expressers is to provide initial tacrolimus dosing of 1.5-2 times the recommended starting dose and to not exceed a starting dose of 0.3 mg/kg/d. CYP3A5 expressers in our study required approximately 1.5 times the recommended FDA-approved 0.14 mg/kg/d starting dose for LCPT to achieve therapeutic tacrolimus trough concentrations[ 6 ]. The majority of CYP3A5 expressers in this study required an approximate 20% reduction in the mean LCPT dose at day 30 from the time of attainment of therapeutic tacrolimus trough concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recommendations for all CYP3A5 expressers is to provide initial tacrolimus dosing of 1.5-2 times the recommended starting dose and to not exceed a starting dose of 0.3 mg/kg/d. CYP3A5 expressers in our study required approximately 1.5 times the recommended FDA-approved 0.14 mg/kg/d starting dose for LCPT to achieve therapeutic tacrolimus trough concentrations[ 6 ]. The majority of CYP3A5 expressers in this study required an approximate 20% reduction in the mean LCPT dose at day 30 from the time of attainment of therapeutic tacrolimus trough concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to immediate release tacrolimus, once daily extended-release formulations have demonstrated similar efficacy and safety in the de novo kidney transplant setting leading to increased utilization[ 1 , 2 , 4 , 5 ]. Life cycle pharma tacrolimus (LCPT) (Envarsus ® ; Veloxis Pharmaceuticals) was designed to enhance the bioavailability of tacrolimus[ 6 ]. In published studies, utilization of LCPT has been shown to provide rapid achievement of target trough concentrations following kidney transplantation[ 1 , 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, the patient was young and a donor was available, leading the patient to undergo a kidney transplant. The patient's immunosuppressive regimen included tacrolimus as the primary choice of agent [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…LCPT formulations would allow greater flexibility in the timing of blood draws for tacrolimus concentrations. Philosophe et al (1) found that blood concentrations taken at both 21 and 27 h post-dose were highly correlated with area under the concentration-time curve over 24 h AUC. The high correlation coefficients found in this study were similar to those found by Gaber et al (3) in a phase 2 study of stable adult kidney transplant patients on IR-Tac who were converted to LCPT.…”
Section: Discussionmentioning
confidence: 99%